Analysis of Students' Difficulties in Reading Comprehension Narrative Text Faced by Ninth Grade Junior High School Students: Analisis Kesulitan Siswa dalam Pemahaman Membaca Teks Narasi yang Dihadapi Siswa Kelas Sembilan SMP - Amirotul Mukminah Suherman; Vidya Mandarani (Academia Open, 2021)
This study aimed to find out the difficulties in reading comprehension of narrative text faced by students ninth-grade at SMP Muhammadiyah 3 Waru. This study used a qualitative descriptive method where data collection techniques is interview. The sample of this study were students of class 9-A SMP Muhammadiyah 3 Waru which consisted of 29 students. However, in this study only 15 students were willing to participate in the interview. The results of this study has shown that students had three difficulties in reading comprehension of narrtive text, namely, students’ difficult to understand the word, difficult to understand long sentences and difficult to understand the main idea.